2012
DOI: 10.1002/bjs.8788
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of outcomes after intraoperative pancreatic duct stent placement during pancreaticoduodenectomy

Abstract: Pancreatic duct stenting did not reduce the incidence of pancreatic fistula and other complications in pancreaticoduodenectomy compared with no stenting. Although no difference was found between external and internal stents in terms of efficacy, external stents seemed to reduce the incidence of pancreatic fistula compared with control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 51 publications
(118 reference statements)
1
56
0
2
Order By: Relevance
“…This modified technique leads us to decrease pancreatic leaks and fistula with the rationale that stenting prevents the accumulation of pancreatic secretions, so the pancreaticojejunostomy is excluded from direct contact with pancreatic juice [14]. Several studies examined the efficacy of internal and external pancreatic stents in preventing POPF but the results are still in contrast [23,24]. POPF is the most important complication of pancreaticoduodenectomy because, directly or indirectly, contributes to the other morbidity including DGE, postpancreatectomy hemorrhage and death.…”
Section: Discussionmentioning
confidence: 99%
“…This modified technique leads us to decrease pancreatic leaks and fistula with the rationale that stenting prevents the accumulation of pancreatic secretions, so the pancreaticojejunostomy is excluded from direct contact with pancreatic juice [14]. Several studies examined the efficacy of internal and external pancreatic stents in preventing POPF but the results are still in contrast [23,24]. POPF is the most important complication of pancreaticoduodenectomy because, directly or indirectly, contributes to the other morbidity including DGE, postpancreatectomy hemorrhage and death.…”
Section: Discussionmentioning
confidence: 99%
“…Some prospective randomized [71][72][73], non-randomized studies and a meta-analysis showed external stents reduced the rates of pancreatic fistula when compared to no stents or internal stents [74][75][76][77]. In a recent meta-analysis by Hong et al (external stents versus no stents) showed no difference in clinical outcome, but reduced the rates of POPF and related morbidity and hospital stay [77].…”
Section: Role Of Stentsmentioning
confidence: 99%
“…However, confirming the published literature, we found that the conclusions were often under debate. So far, five meta-analyses [18,19,20,21,22] on this topic have been already performed to evaluate perioperative outcomes, but those conclusions might be not reliable enough for clinical decision-making as they are based on both RCTs and observational studies. There were not even any relatively indispensable interpretations of subgroup analysis or sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%